Hot-cell clusters deriving algorithm for slow dynamic channel allocation - SHI Wen-xiao; JIN Tao; CHI Xue-fen; FAN Shao-shuai (Tongxin xuebao)
Aiming at overcoming the shortages of the current slow dynamic channel allocation algorithm in TD-SCDMA system,hot cell clusters deriving algorithm was proposed.The algorithm constituted a multi-cell system model through the way that the hot cells were continuously derived to resolve the identification and expansion problem of the hot cell clusters.As the result,system capacity is increased.The simulation results show that,the hot cell clusters deriving algorithm can adapt to different service distribution models well.Compared to the hot cell algorithm,the system resource utilization is increased by 3.8 percent.